Transcriptome analysis reveals nutrient deprivation reduces nitrate content in lettuce (Lactuca sativa var. ramosa Hort.) and enhances nitrogen metabolism - Zhang, Yingying; Liu, Xuena; La, Shikai; Wang, Mingjiao; Hu, Xu; Shi, Ainong; Guo, Jinghua; Dong, Lingdi (Frontiers in Plant Science, 2025)
IntroductionExcessive nitrate accumulation in leafy vegetables poses health risks and indicates inefficient nitrogen use in conventional agriculture. While nitrogen metabolism has been extensively studied, the molecular mechanisms linking nutrient deprivation to nitrate reduction in vegetables remain unclear.MethodsIn this study, we investigated these mechanisms in lettuce (Lactuca sativa var. ramosa Hort.) by analyzing nitrate content and gene expression in leaves and roots under nutrient deprivation.ResultsAfter five days of treatment, nitrate content decreased by 57.49% in leaves and 50.77% in roots. Transcriptome sequencing identified 323 and 3,494 differentially expressed genes (DEGs) in leaves and roots, respectively, with 78 shared DEGs. KEGG enrichment analysis revealed involvement of DEGs in pyrimidine metabolism, base excision repair, hormone signaling, terpenoid biosynthesis, and triglyceride metabolism, indicating cross-talk between nitrate regulation and stress responses. Nitrate transporter genes NRT2.4 and NRT2.5 were upregulated in roots, while NRT1 was induced in leaves, suggesting enhanced nitrate redistribution. Additionally, antioxidant genes such as POD, LOX, and cytochrome P450 were upregulated in roots, whereas SODC was downregulated in both tissues. These results suggest that lettuce responds to nutrient deprivation by activating nitrate transport and antioxidant pathways to reduce nitrate levels and enhance nitrogen use efficiency.DiscussionThis study provides a foundation for optimizing pre-harvest strategies to improve lettuce quality and identifies candidate genes (e.g., NRT2.5, LOX) for breeding low-nitrate varieties suited for nitrogen-limited environments.